Clinical factors associated with contact lens dropout. Issue 3 (June 2019) - Pucker, Andrew D.; Jones-Jordan, Lisa A.; Marx, Sebastian; Powell, Daniel R.; Kwan, Justin T.; Srinivasan, Sruthi; Sickenberger, Wolfgang; Jones, Lyndon; ,
Abstract: Purpose: Contact lens (CL) dropout is estimated to be approximately equal to the number of new wearers per year, resulting in virtually no growth in the global CL market. The purpose of this study was to determine ocular and CL factors associated with CL dropout. Methods: This five-site study recruited subjects 18–45 years of age who had ceased CL wear within the past 6–12 months due to discomfort. Dropout subjects were compared to age- and sex-matched currently successful CL wearers. Each subject was administered a symptoms survey and a study-specific survey that queried general CL history and compliance. Clinical testing included non-invasive tear break-up time, tear meniscus height, blepharitis assessment, meibum quality and expression, and meibography. Results: A total of 56 matched-pairs were recruited. Dry eye was found to significantly increase a subject's odds of dropping out of CLs. The odds of dropping out of CLs was also significantly increased with each worsening grade of upper or lower eyelid meibomian gland (MG) plugging, upper eyelid meibum quality, and upper eyelid MG tortuosity. No other factors analyzed increased a subject's odds of dropping out of CLs. Conclusions: CL dropout may be precipitated by underlying dry eye symptoms, though most dry eye signs, with the exception of MG structure and function, had minimal predictive value for CL dropout. Nevertheless, evidence suggests that practitioners should screen for and educate CL patients about the importance of maintaining healthy MGs, which may potentially allow them to maintain comfortable CL use and increase their CL longevity.